2020
DOI: 10.1177/0960327120938851
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to paraquat associated with periodontal disease causes motor damage and neurochemical changes in rats

Abstract: Exposure to paraquat is possibly involved with the development of several conditions, including neurodegenerative diseases, such as Parkinson’s disease (PD). This condition is mainly characterized by the loss of dopaminergic neurons in the nigrostriatal pathway and the development of classical motor symptoms. Etiology includes exposure to environmental factors, such as the paraquat exposure, and inflammatory diseases may exacerbate paraquat neurotoxicity. The aim of the study was to investigate whether the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…In all cases, it was reported that paraquat increased the release of ROS due to mitochondrial damage, which induced oxidation of lipids, proteins, and nucleic acids, in addition to increase inflammatory responses, and in some cases, apoptosis, which led to the development of ulcers of the oral mucosa and bleeding [ 61 , 62 , 63 , 64 , 65 ]. The increases in oxidative stress and inflammation are responses that were also observed in a murine model exposed to paraquat, and they are very similar to those seen in the pathology of periodontitis with loss of the alveolar bone [ 52 ].…”
Section: General Effects Of Pesticides On the Oral Cavitymentioning
confidence: 83%
See 4 more Smart Citations
“…In all cases, it was reported that paraquat increased the release of ROS due to mitochondrial damage, which induced oxidation of lipids, proteins, and nucleic acids, in addition to increase inflammatory responses, and in some cases, apoptosis, which led to the development of ulcers of the oral mucosa and bleeding [ 61 , 62 , 63 , 64 , 65 ]. The increases in oxidative stress and inflammation are responses that were also observed in a murine model exposed to paraquat, and they are very similar to those seen in the pathology of periodontitis with loss of the alveolar bone [ 52 ].…”
Section: General Effects Of Pesticides On the Oral Cavitymentioning
confidence: 83%
“…In patients with periodontal disease, there are increase in the well-known red, orange, and yellow complexes ( Table 2 ). The first two complexes are associated with severe and moderate periodontal disease, while the yellow complex is associated with lower virulence [ 1 , 35 , 41 , 43 , 51 , 52 ].…”
Section: Oral Cavitymentioning
confidence: 99%
See 3 more Smart Citations